PENGARUH BELANJA DAERAH DAN PENDAPATAN PERKAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - B01112046, Misra Armaniah (Jurnal Pembangunan dan Pemerataan, 2016)
Development is a process carried out by the government to implementvarious policies to achieve the goals of public welfare and make a change towardsa better future. The expected changes are among others to improve the quality ofhuman life in a country or region, so that the ultimate goal of a developmentprocess improve the welfare of the people through improving the quality ofhuman life can be achieved. Human Development Index (HDI) can be used as anindicator to measure the level of welfare. This research aims to analyze the effectof regional expenditures and per capita income on Human Development Index(HDI) of the Regenies / cities in the province of West Kalimantan. This researchemployed quantitative descriptive method using a linear regression model andstatistical analysis i.e coefficient of determination (R2), F-test and t- test toexamaine the hypothesis whether regional expenditure the and per capita incomehad effect on the HDI.These results indicate that the regional spending in education haspositive effect amounting to 0.014929 and significant , regional healthexpenditures amounted to 0.007631 and the positive effect was not significant andper capita income has positive effect amounting to 0.136006 and significant onthe HDI of regencies/cities in West Kalimantan province. the value ofdetermination cocfficicnt was 0.450596 . This means that the variable regionalspending in education, regional health expenditures and per capita income couldexplain the variable of HDI of 45.06 % , whereas the remaining 54.94 % could beexplained by other variables such as economic growth , percentage of poverty andother variables that were not included in the modelKeywords : Regional Expenditure, Per- capita Income and Human DevelopmentIndex (HDI)